Distrito Uranífero Sierra Pintada. San Rafael-Mendoza - Ortega Furlotti, A.; Baluszka, Juan Carlos; Pérez, E. Enrique; Giordano, Norberto Luis (Comisión Nacional de Energía Atómica; Argentina, 1978)
Fil: Ortega Furlotti, A. Comisión Nacional de Energía Atómica; Argentina